Designing of technological process of concreting of vertical structures of a monolithic building - Basarab, V.; Umanets , I. (Ways to Improve Construction Efficiency, 2021)
The article is devoted to design of technological process of concreting the vertical structures of a monolithic building. The technology of construction the reinforced concrete structures today is widespread. A necessary condition for design of technological process of building construction is the use of information computer-aided design technology. The use of software allows you to solve more effectively a number of problems in design of technological processes of building construction, namely: variant design, search for optimal solutions, forecasting. The urgency of determining the rational parameters of the multivariate technological process of building constructions and structures by use of software of technological design was emphasized. Determination of the rational number of workers and scaffolding in the concreting of vertical monolithic structures of building by comparing such criteria as cost of construction and its complexity has been performed. The scheme of working area and construction-technological analysis of basic parameters of the monolithic building has been given. Modern Fortran software has been used to calculate the parameters of multivariate technological problems. The mathematical equations for calculation of the basic technological parameters of construction process of a monolithic building has been given. An algorithm for performing calculations has been developed. A program has been developed to determine the general characteristics of the concreting process (volume of monolithic works, time of concreting elements, cost and labor intensity, number of units and number of workers). Analyze of technological parameters and the choice on their basis the rational technological solutions for construction work has been performed by using of Microsoft Excel graphs. According to the results of research, a rational number of workers and scaffolding for concreting vertical monolithic structures of building has been determined by comparing such criteria as cost of construction and complexity.